2017
DOI: 10.1186/s12885-016-2997-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between telomere length and the risk of colorectal cancer: a meta-analysis of observational studies

Abstract: BackgroundHuman chromosomes are capped and stabilized by telomeres. Telomere length regulates a ‘cellular mitotic clock’ that defines the number of cell divisions and hence, cellular life span. This study aimed to synthesize the evidence on the association between peripheral blood leucocytes (PBL) telomere length and the risk of colorectal cancer (CRC).MethodsWe searched relevant studies in electronic databases. When two or more observational studies reported the same outcome measures, we performed pooled anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Long telomeres is a risk factor for glioma, lung, ovarian, testicular, kidney, skin, endometrial and neuroblastoma cancers [9]. For CRC, observational studies find no evidence of an association between short or long telomeres and disease development [10]. Using genetically predicted telomere length in a so called Mendelian Randomization analysis, unconfounded associations with CRC where confirmed negative [9].…”
mentioning
confidence: 99%
“…Long telomeres is a risk factor for glioma, lung, ovarian, testicular, kidney, skin, endometrial and neuroblastoma cancers [9]. For CRC, observational studies find no evidence of an association between short or long telomeres and disease development [10]. Using genetically predicted telomere length in a so called Mendelian Randomization analysis, unconfounded associations with CRC where confirmed negative [9].…”
mentioning
confidence: 99%
“…Nevertheless, a study demonstrated an U-shaped association between TL and colorectal cancer initiation (28). On the basis of the combination of 8 datasets, a meta-analysis showed that TL was not contributed to colorectal cancer risk (29). Hence, the relationship between TL and colorectal cancer development needs to further investigate.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between telomere length and colorectal risk has largely been studied by measuring telomere length in peripheral blood leukocytes and there is considerable heterogeneity in results across studies [ 30 ]. Prospective studies of this relationship have consisted of three case-control studies, nested within existing large cohorts, which have measured telomere length in stored blood samples collected at recruitment [ 37 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some traditional case-control studies have shown short telomeres are associated with increased risk of colorectal cancer [ 39 , 41 , 42 ]; yet, other case-control studies have shown that both short and long telomeres are related to increased colorectal cancer risk [ 43 , 44 ]. Collectively, these results indicate that the relationship between telomere length and colorectal cancer risk may be complex and suggest that telomere length, at least as measured in peripheral blood leukocytes, is not strongly related to colorectal cancer risk years later [ 30 ]. Telomere dynamics in colonocytes differ from those in other tissues, specifically those of peripheral blood leukocytes [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation